Isbat Nikah dalam Undang-Undang Perkawinan - Nopitasari; Kairuddin Karim; Muhammad Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2022)
The opportunity for marriage itsbat is one of the means for perpetrators or irresponsible persons who violate the marriage law. This study aims to determine the position of marriage itsbat according to Law Number 1 of 1974. This study uses a normative research type with a statutory approach and a case study approach, the data collection techniques used are interviews and documentation. The results of the study indicate that the application for ratification of marriage itsbat by the judge in the determination of Number 74/Pdt.P/2021/PA.Pare by the applicants is declared valid according to law. Marriage between husband and wife to legalize their marriage following Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage that the marriage is legal according to law